Comparison of the Real-Driving Emissions (RDE) of a Gasoline Direct Injection (GDI) Vehicle at Different Routes in Europe - Barouch Giechaskiel; Victor Valverde; Anastasios Melas; Michaël Clairotte; Pierre Bonnel; Panagiota Dilara (Energies, 2024)
On-road real-driving emissions (RDE) tests with portable emissions measurement systems (PEMS) are part of the vehicle emissions regulations in the European Union (EU). For a given vehicle, the final emission results depend on the influence of the ambient conditions and the trip characteristics (including the driver’s behaviour) on the vehicle performance and the instrument measurement uncertainty. However, there are not many studies that have examined the emissions variability of a single vehicle following different routes. In this study, a 1.2 L gasoline direct injection (GDI) Euro 5b passenger car without a particulate filter and a PEMS was circulated in seven European laboratories. At their premises, the laboratories performed two to five repetitions of on-road trips compliant with the EU RDE regulation. The ambient temperature ranged between 7 °C and 23 °C. The average emission levels of the vehicle were 135 g/km for CO2, 77 mg/km for CO, 55 mg/km for NOx, and 9.2 × 1011 #/km for particle number. The coefficient of variance in the emissions following the same route was 2.9% for CO2, 23.8% for CO, 23.0% for NOx, and 5.8% for particle number. The coefficient of variance in the emissions following different routes in Europe was 6.9% for CO2, 9.1% for CO, 0.0% for NOx, and 9.1% for particle number. The previous values include the specific vehicle emissions variability under the narrow test conditions of this study, but only partly the PEMS measurement uncertainty because the same instrument was used in all the trips. The results of this study can be used by laboratories conducting RDE tests to assess their uncertainty budget when testing or comparing vehicles of similar technology.